2021
DOI: 10.3390/brainsci11040480
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Attentional Processes: The Role of Resting Heart Rate Variability

Abstract: Individuals with high anxiety preferentially focus attention on emotional information. The autonomic nervous system (ANS) plays an important role in modulating both anxiety and attentional processes. Despite many studies having evaluated attentional bias in anxious people, few of them have investigated the change blindness phenomenon associated with the attentional response toward salient stimuli, considering the role of the ANS. This study aimed to examine the role of heart rate variability (HRV) in trait anx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 65 publications
1
26
0
Order By: Relevance
“…The 15 studies selected were conducted from 2010 (Brunborg et al, 2010) to 2021 (Forte, Favieri, et al, Sütterlin et al, 2011a;Sütterlin et al, 2011b;Dunn et al, 2012;Ramírez et al, 2015;Steenbergen et al, 2020;Forte, Favieri, et al, 2021; and 65 years (Dunn et al, 2012), and with a percentage of men in the studies varying between 29% (Dunn et al, 2012) and 100% (Laborde & Raab, 2013).…”
Section: Demographic Datamentioning
confidence: 99%
See 2 more Smart Citations
“…The 15 studies selected were conducted from 2010 (Brunborg et al, 2010) to 2021 (Forte, Favieri, et al, Sütterlin et al, 2011a;Sütterlin et al, 2011b;Dunn et al, 2012;Ramírez et al, 2015;Steenbergen et al, 2020;Forte, Favieri, et al, 2021; and 65 years (Dunn et al, 2012), and with a percentage of men in the studies varying between 29% (Dunn et al, 2012) and 100% (Laborde & Raab, 2013).…”
Section: Demographic Datamentioning
confidence: 99%
“…Recent reviews showed that HRV and cognitive performance are positively related (Forte et al, 2019; Grässler et al, 2020). Higher resting HRV is associated with better cognitive performance and a broader self‐control ability (Forte, Favieri, et al, 2021; Forte, Morelli, & Casagrande, 2021; Maier & Hare, 2017). The centrality of the ventromedial prefrontal cortex (vmPFC) in decision‐making and its control over cardiac activity suggests that HRV could be a marker of individuals' ability to make decisions, especially under risk and under conditions of uncertainty.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors of the NVIM proposed a core set of neural structures, referred to as the Central Autonomic Network (CAN), which provides the ability to continuously assess and prepare the organism for an appropriate response [ 18 ]. In the NVIM, heart rate variability (HRV) has been proposed as an index of flexible and adaptive regulation of the nervous system to organize a homeostatic response to environmental requests and which is related to cognitive functions [ 18 , 19 , 20 , 21 , 22 ]. HRV represents the change in the time interval between successive heartbeats.…”
Section: Introductionmentioning
confidence: 99%
“…State anxiety is associated with increased local functional connections within the posterior regions of the DMN, such as the precuneus and posterior cingulate cortex. A recent physiological study has provided additional evidence that, as the power of high-frequency HRV for prefrontal inhibition increases, cognitive/motor performance is improved in people with higher trait anxiety [ 81 ]. To summarize these findings, on the one hand, participants reporting higher trait anxiety may activate a prefrontal inhibition system to suppress automatic emotional reactivity during the IGT and produce a more negative association between model fitting coefficients and trait anxiety scores.…”
Section: Discussionmentioning
confidence: 99%